Weak hydrogen bonds on CF enhancing interfacial strength and toughness for CFRPs. (5th January 2023) - Pu, Yinchuan; Ma, Zhenyu; Liu, Li; Bai, Yongping; Huang, Yudong
Abstract: It was a major challenge to acquire CFRPs with both great toughness and strength. Inspired by spider silk, a biomaterial with impressive toughness, we discovered that introducing highly dense weak hydrogen bonds at the interface can be applied to CFRPs toughening. Highly dense weak hydrogen bonds between the branched polyethyleneimine (PEI) and metal-organic frameworks UIO-66 at the interface of CFRPs were formed by the "bridge" of hydroxyl-rich poly (vinyl alcohol) (PVA). The break of those hydrogen bonds could dissipate substantial energy and disperse the stress, the impact toughness of CFRPs with the "PEI-PVA-UIO-66" interlayer was up to 99.53 kJ/m 2 . Compared with composites reinforced by CFs modified with UIO-66 by chemically grafting or by physically absorbing without PVA, the impact toughness of CF-PVA-MOF/EP improved by 45% and 33%, respectively. This means that the highly dense weak hydrogen bonds have superiority for CFRPs toughening. Meanwhile, the interfacial shear strength (100.85 MPa) and interlaminar shear strength (102.44 MPa) of CFRPs were realized by the innovative designed interfacial structure. Graphical abstract: Image 1 Highlights: The interphase of polyvinyl alcohol, polyethyleneimine and UIO-66 with rich hydrogen bonds was designed on CFs. The presence of highly dense weak hydrogen bonds at the interface has superiority in toughening CFRPs. The impact toughness and interface performance of CFRPs were improved simultaneously with no loss of fiber tensile strength.